Effect of host plant on biology and life table parameters of Sipha maydis (Pass.) (Hemiptera: Aphididae) - La Rossa, Francisco Ruben; Giudici, Albano Cesar; Vasicek, Araceli; López, María Carolina; Bainotti, Carlos Tomas (2017)
Sipha (Rugsia) maydis (Pass.) is an important pest of wheat and it has been reported throughout the Mediterranean region, into Central and South Asia, South Africa, South America and North America The development, survivorship, and life table parameters of R. padi were evaluated in a growth chamber on seven wheat cultivars as follows: ACA 315, Baguette 12 P, BioINTA 1002, BioINTA 2004, Buck Meteoro, Klein Yarará and LE 2330 at controlled conditions (20±1°C; about 70% RH; 14 h photophase). The development time of immature stage was ca. 8-9 d on cv. ACA 315, BioINTA 1002, Buck Meteoro, Klein Yarará and LE 2330, while those on cvs BioINTA 2004 and Baguette 12 P was ca. 11-12 d. The immature survival ranged from 90 to 100%. The intrinsic rate of increase (rm) for ACA 315 and BioINTA 2004 were the highest. Jackknife estimates of rm on all cultivars ranged from 0.199 to 0.093 females/female/day on ACA 315 and LE 2330, respectively. The mean generation times (T) ranged from 22.82 d on Baguette 12 P to 15.09 d on Klein Yarará. The highest net reproductive rate (R0) were on ACA 315 and Baguette 12 P (59.80 and 53.25 females/female/generation, respectively). Because of the high coefficient of determination (pseudo-R2) values in Gompertz and Weibull models, survival data from different cultivars had a good fit to both models. The results pointed LE 2330, Klein Yarará and partially BioINTA 1002 as the least suitable host plants, indicating that they were the most resistant to S. maydis among the cultivars tested.